Influence of geometrical parameters on thermal-hydraulic performance and entropy generation in cross-wavy channels with variable air properties. (5th July 2019) - Shi, Xusheng; Wang, Yongwei; Huai, Xiulan; Cheng, Keyong
Highlights: Thermal-hydraulic performance on cross-wavy channel were discussed. Entropy generation analysis on cross-wavy channel were discussed. The larger ratio of amplitude to length, the smaller total entropy generation. The larger ratio of height to pitch, the smaller total entropy generation. The lower Reynolds number, the smaller total entropy generation. Abstract: In the study, the effects of the ratio of channel amplitude to wavelength ( A/L ) and channel height to pitch ( H/P ) of cross-wavy (CW) channels on thermal-hydraulic performance and entropy generation rate are investigated numerically. The low Reynolds number k-ε (LBKE) turbulent model is adopted. The studied cases cover five types of CW channel with Reynolds number ( Re ) range of 200–1200. The results show that the heat transfer is enhanced with increasing A/L value at the same H/P . Meanwhile friction factor increases with increasing A/L . Similarly, increase of H/P makes the heat transfer enhance at the same A/L . However, the friction factor is almost unchanged with increasing H/P value. In addition, the flow and heat transfer reaching fully developed are fast in CW channels which causes the consequence that much entropy generation concentrates at the first flow units of channels. Thermal irreversibility is main part of total irreversibility in CW channels. It is lower with increasing A/L at the same H/P value and lower with increasing H/P at the same A/L value. In conclusion, the type of larger A/L and H/P value and lower Reynolds number are suggested to be used, so that the minimum irreversibility could be achieved.